Implikasi Garar dan Maisir di Hukum Islam - Magfirah, Khofifah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines the application of Islamic law's prohibition on gharar (uncertainty) and maisir (gambling) in contemporary economic transactions. The prohibition of these two elements in Islam is a form of self-protection based on the principles of sharia (maqasid sharia), particularly in protecting property (hifzhul mal) and preventing economic exploitation and injustice in trade. This article uses a qualitative approach based on library research of primary and secondary sources in Islamic jurisprudence (fiqh) of muamalah. The results of this research indicate that gharar and maisir have clear definitions, standards, and levels in classical muamalah jurisprudence. In contemporary practice, conventional insurance systems and social insurance programs such as BPJS Kesehatan (Social Security Agency) contain elements of gharar and maisir, which are considered intelligent and offer benefits. Under Islamic law, a contract or agreement containing these elements is considered fasid and invalid. This prohibition is due to the potential harm to one of the parties and does not reflect the values of justice and mutual consent (antaradin) in the transaction. Therefore, reformulation of the economic system in accordance with Islamic law must be carried out immediately to ensure that Muslim transactions do not involve prohibited practices and remain within the corridor of Islamic law.